2020
DOI: 10.1039/d0fo00238k
|View full text |Cite
|
Sign up to set email alerts
|

Stability andin vitrosimulated release characteristics of ultrasonically modified soybean lipophilic protein emulsion

Abstract: Ultrasonically modified soybean lipophilic protein has improved solubility and emulsifying properties, which are advantageous for preparing emulsions that improve the bioavailability of vitamin E while protecting its biological activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 48 publications
3
13
0
Order By: Relevance
“…The decrease in emulsifying activity was attributed to protein aggregation caused by excessive ultrasound. This result was similar to soybean protein [26] .…”
Section: Resultssupporting
confidence: 84%
“…The decrease in emulsifying activity was attributed to protein aggregation caused by excessive ultrasound. This result was similar to soybean protein [26] .…”
Section: Resultssupporting
confidence: 84%
“…4, compared with other protein hydrolysates, UBPH-4 presented the lowest content of α-helix and the highest content of random coil, which is consistent with the results of FTIR. This further demonstrated that ultrasound pretreatment disrupted connections among local sequences of amino acids, resulting in the disaggregation of the BSGP structure (Li et al, 2020). Consequently, ultrasound stimulated the exposure of BSGP to Alcalase, facilitating the conversion of hydrolysate, which agreed with the DH analysis (Fig.…”
Section: Spectroscopysupporting
confidence: 77%
“…Ultrasonication is a powerful physical method that can affect the intramolecular bonds of proteins, and even disrupt their molecular structures [13] , [14] . Li et al [15] found that the ultrasonic treatment could denature the soybean prolipoprotein but with significantly improved solubility in water under certain conditions due to its cavitation and mechanical effects, which was confirmed by circular dichroism (CD) analysis for the changes of the secondary and tertiary structures of the protein. Wu et al [16] studied the effects of ultrasonication on the physicochemical properties of whey protease, and found a higher degree of hydrolysis of whey protein after the treatment, indicating that the ultrasonic treatment could be applied to facilitate the breakdown of whey proteins for other applications, such as development of novel functional foods.…”
Section: Introductionmentioning
confidence: 91%